The involvement of palliative care with neurology – a comparison of UK, Switzerland and Italy. Issue 3 (3rd April 2023) - Oliver, David; Baker, Idris; Borasio, Gian Domenico; Cras, Patrick; Faull, Christina; Hepgul, Nilay; Lorenzl, Stefan; Stockdale, Claire; de Visser, Marianne; Vanopdenbosch, Ludo; Voltz, Raymond; Veronese, Simone
Abstract: Objectives: To ascertain the involvement of palliative care with neurology services in the care of people with amyotrophic lateral sclerosis (ALS) in the United Kingdom, Italy and Switzerland, in particular the collaboration with and referral from neurology, the involvement in multidisciplinary team care and in the respiratory support of ALS patients. Methods: In 2019, two online surveys were undertaken of palliative care specialists, using specialist groups of the European Academy of Neurology, European Association of Palliative Care and the Association of Palliative Medicine for Great Britain and Ireland. Results: The respondents were specialist palliative care professionals, predominantly senior doctors, involved in the care of people with ALS. As the numbers of respondents from many countries were in single figures the analysis was restricted to the United Kingdom, Italy and Switzerland. The time of involvement varied, with early involvement commonest in the UK. Barriers to referral included neurologists not referring and financial issues, particularly in Switzerland. The reluctance of patients and families to see palliative care services was reported as less than 20% in all countries. Respondents were often involved in the care of people receiving noninvasive ventilation (NIV), in all countries. and with tracheostomy ventilation (TV), particularly in Italy. Conclusions: Palliative care services are often involved in the care of people with ALS, but the extent and timing of involvement varies. The use of clinical guidelines and education on palliative care for neurology services may encourage collaboration, for the benefit of people with ALS and their families.